Sharing is Caring: An Exploration of Motivations for Social Sharing and Locational Social Media Usage among Sport Fans - Galen Clavio; Evan Frederick (Journal of Applied Sports Management, 2014)
The purpose of this study was to examine motivations for social sharing and using locational social media within the framework of uses and gratifications. Specifically, fans of five college football teams were surveyed regarding social sharing and their use of locational social media applications. Exploratory factor analysis revealed two factors for the social sharing of sport-related check-ins, including promotion, fanship, and personal gain. Regarding incentives for the future use of locational social media and social sharing, fans revealed that they were motivated by recognition and monetary factors. The findings indicated a strong desire among fans to feel a sense a community and receive recognition when engaging in social sharing or using locational social media applications. These and other findings are discussed, and recommendations for sport organizations interested in promotion of social sharing are provided.
Keywords: locational social media; social sharing; sport communication; fanship; community